PREJUDICE AND DISCRIMINATION AGAINST WOMEN IN THE MUSIC MARKET - D´Amorim, Ramon Schnayder de França Filgueiras; da Silva, Ricardo Moreira; Moreira, Josilene Aires (Seven Editora, 2025)
The study stemmed from the need to listen to women's voices and how they express themselves, how they enjoy the desired autonomy, freedom, and equality, while often submitting to male power. The analysis of the Paraíba music scene is historically marked by male dominance, where men and women clearly lack equal opportunities for participation. This study aimed to analyze the participation of female artists in the Paraíba music market, revealing a scenario still marked by gender inequalities. The theoretical framework was grounded in studies that reflect on music as one of the most closely related cultural manifestations of everyday life and how it can be directly affected by determinations that affirm or challenge prevailing models and customs at a given historical moment, contributing to an understanding of the factors of gender and sexual orientation and how they can be expressed in the musical production of men and women. The methodology used was based on content analysis of open-ended responses in structured interviews, supported by the use of the Likert Scale. The results demonstrated that discrimination and prejudice, access to funding, and support for registering works have fueled the struggle for rights and recognition and are gaining ground in Brazil and Paraíba, reducing disadvantages for women in both the social and musical arenas. The research indicated that women still face internal and external obstacles to their careers, balancing family responsibilities with the pursuit of diverse creative outlets to enrich their artistic journeys.DOI: https://doi.org/10.56238/sevened2025.029-052